Reduced Renal Mass, Salt-Sensitive Hypertension Is Resistant to Renal Denervation - Tudorancea, Ionut; Lohmeier, Thomas E.; Alexander, Barbara T.; Pieptu, Dragos; Serban, Dragomir N.; Iliescu, Radu (Frontiers in Physiology, 2018)
Aim. Activation of the sympathetic nervous system is common in resistant hypertension and also in chronic kidney disease, a prevalent condition among resistant hypertensives. However, renal nerve ablation lowers blood pressure only in some patients with resistant hypertension. The influence of loss of nephrons per se on the antihypertensive response to renal denervation is unclear and was the focus of this study. Methods. Systemic hemodynamics and sympathetically-mediated low frequency oscillations of systolic blood pressure were determined continuously from telemetrically acquired blood pressure recordings in rats before and after surgical excision of 80% of renal mass and subsequent renal denervation. Results. After reduction of renal mass, rats fed a high salt diet showed sustained increases in mean arterial pressure (108 +/- 3 mmHg to 128 +/- 2 mmHg) and suppression of estimated sympathetic activity ( 15%), responses that did not occur with high salt before renal ablation. After denervation of the remnant kidney, arterial pressure fell (to 104 +/- 4 mmHg), estimated sympathetic activity and heart rate increased concomitantly, but these changes gradually returned to pre-denervation levels over 2 weeks of follow up. Subsequently, sympathoinhibition with Clonidine did not alter arterial pressure while significantly suppressing estimated sympathetic activity and heart rate. Conclusions. These results indicate that renal denervation does not chronically lower arterial pressure in this model of salt-sensitive hypertension associated with substantial nephron loss, but without ischemia and increased sympathetic activity, thus providing further insight into conditions likely to impact the antihypertensive response to renal-specific sympathoinhibition in subjects with chronic kidney disease.